Implementation of Sales Promotion Strategies to Enhance Speed Jersey Sales on Shopee Marketplace - Mustaghfiroh, Tsalitsah Alifah; Junipriansa, Donni (Fakultas Ekonomi Universitas Garut, 2024)
In 2020, Indonesia experienced a major shock due to COVID-19 which resulted in all activities being suspended. This has an impact on many aspects, one of which is the economy. Many businesses experience a decline in sales in a very short period of time. So, they need to carry out various business innovations to survive in difficult times, one of which is by utilizing the internet. The significant decline in Speed Jersey sales is certainly a problem that needs to be handled effectively. One of the marketing strategies used by Speed Jersey in the Shopee marketplace is using Sales Promotion. The research that the author uses is descriptive qualitative research. Based on the results of the interview, it shows that Speed Jersey sales increased due to the implementation of Sales Promotion using coupons and discounts on the Shopee marketplace. It can be drawn meaning that sales are determined by various factors. Sales promotion factors are one of the most important to increase profits in a company. Many promotional media can be done to attract customers, one of which is giving coupons and discounts.